Corporate Governance Mechanisms and Financial Performance: A Systematic Literature Review in Emerging Markets - Mahmudi, Bambang (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the relationship between corporate governance mechanisms and financial performance in emerging markets. Through a systematic literature review approach, researchers analyze various studies that have been conducted to understand the role of board of directors composition, institutional ownership, and financial reporting transparency in influencing company performance. The findings show that a diverse board of directors composition, strong institutional ownership, and financial reporting transparency have a significant impact on a company's financial performance. Apart from that, the relationship between corporate governance and financial performance is also supported by various theories such as agency theory, stewardship and collective action. This research provides a better understanding of the importance of effective governance practices in achieving sustainable financial performance in emerging markets.